Changes in genomic inbreeding and diversity over half a century in Swedish Red and Swedish Holstein dairy cattle. (16th January 2023) - Eriksson, Susanne; Strandberg, Erling; Johansson, Anna M.
Abstract: Swedish Red (SR) and Swedish Holstein (SH) are the dominating commercial dairy cattle breeds in Sweden. Both breeds have undergone substantial changes during the last half century due to intensive selection for breeding goal traits, but also resulting from increased international exchange of breeding animals and genetic drift. The aim of this study was to learn more about changes in genomic diversity and inbreeding in these two breeds over time. Therefore, semen samples from old bulls were genotyped using the 150K Genomic Profiler SNP array and combined with 50K SNP array genotype data, obtained for more recent bulls from the Nordic Cattle Genetic Evaluation. Different measures of level of homozygosity, genomic inbreeding, relatedness and changes in allele frequency were estimated for bulls born during different time periods from the 1950s until 2020. In total, more than 33, 000 SNPs for 9737 SR and 5041 SH bulls were included in the analysis using PLINK v1.9. The results showed higher average homozygosity for SR than for SH bulls up to around 2000, but the difference was very small after that. The average inbreeding coefficients based on deviation from expected homozygosity as well as on runs of homozygosity decreased until the early 1980s in both breeds, whereafter they started to increase again for SH, but stayed more stable for SR. From the 1990s onwards, SH displayed higher average inbreeding coefficients than SR. In the last studied birth year group (2015–2020), the mean inbreeding coefficient based on runs of homozygosity was 5.9% for SH and 3.7% for SR. A principal component analysis showed a pattern of genetic relationships related to the birth year period of the bulls, illustrating the gradual change of the genetic material within each breed. The change in allele frequency over time was generally larger for SH than for SR. The results show that the inbreeding level was higher half a century ago than at present, and the inbreeding levels were lower than in some other studied populations. Still, the increase seen for inbreeding coefficients and homozygosity, especially in SH during recent years, should be considered in future breeding strategies.